Takaful protection for mental health illness from the perspective of Maqasid Shariah: A critical analysis / Khairil Faizal Khairi...[et al.] - Khairi, Khairil Faizal; Laili, Nur Hidayah; Sabri, Hisham; Ali Basah, Mohd Yazis; Asmaddy Haris, Mohd Yazis; Mirza, Azrul Azlan Iskandar; Abdul Samat, Mohamad Subini; Shaari, Rosli (UiTM Cawangan Johor, 2019)
Mental health illness becomes one of the major illness in Malaysia aside from heart disease. Recently reported that 29.2% of Malaysian suffering from mental health illness which increases threefold from the previous year. Majority of the Malaysian suffering from mental health illness comes from the lowest income group. This shows that the lowest income group have less opportunity to seek treatment due to the cost. Even though other countries have started to offer mental health insurance such as United State of America, United Kingdom, Australia and recently Singapore, Malaysia is still way behind in offering coverage for mental health illness. Therefore the objective of this paper is to analyse mental health takaful from the perspective of Maqasid shariah. This paper uses a qualitative approach by analysing the related document and past literature. The result from this study shows that mental health takaful is able to meet the requirement of Maqasid shariah and preserve the benefits of, and prevent harm to, human wellbeing. Furthermore this study will provide an insight to the takaful industry for developing a new products that could help mental health disorder patient.